2018
DOI: 10.1111/1747-0080.12501
|View full text |Cite
|
Sign up to set email alerts
|

Availability and composition of weight‐loss supplements in Sri Lanka

Abstract: Aim The present study aims to investigate the composition and availability of weight‐loss supplements in Sri Lanka and explore the evidence for their effectiveness. Methods Data were collected by visiting drug stores, searching the Internet for websites and referring to advertisements in national newspapers and magazines from August to October 2017. Results A total of 100 weight‐loss products were identified of which the majority (n = 57) were available from drug stores. Most commonly, products were available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
(77 reference statements)
0
10
0
1
Order By: Relevance
“…Obesity and overweight are major contributors to the global burden of chronic diseases and complications [ 44 ]. Thus, edible and medicinal plants and their bioactive components helping people to fight the battle against obesity have been widely explored, such as the extracts of garcinia, green tea and white bean [ 13 , 14 , 15 ]. The present investigation showed that F. mandshurica seed extract containing secoiridoids reduced body weight and lipid levels in serum and liver, alleviated liver and kidney damage and regulated the gut microbiota in high-fat diet-induced obese mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity and overweight are major contributors to the global burden of chronic diseases and complications [ 44 ]. Thus, edible and medicinal plants and their bioactive components helping people to fight the battle against obesity have been widely explored, such as the extracts of garcinia, green tea and white bean [ 13 , 14 , 15 ]. The present investigation showed that F. mandshurica seed extract containing secoiridoids reduced body weight and lipid levels in serum and liver, alleviated liver and kidney damage and regulated the gut microbiota in high-fat diet-induced obese mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, several clinical and epidemic studies have shown that maintaining long-term lifestyle modification is a great challenge to obese patients [ 11 ]. Pharmacotherapy can provide an easy way to accelerate weight loss, hence natural supplements derived from plants or synthetic chemicals have become a better choice for obesity treatment [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…This highlights the continual search by those seeking weight loss for a ‘magic bullet’ that will resolve the problem with minimal changes to other facets of their lives. The article is a timely reminder that dietitian‐nutritionists need to understand the types of supplements on the market, the claims they are making and the potential for adverse effects . Claims were not monitored, and given their broad availability, strengthening the global regulatory framework around their distribution and marketing needs to be prioritised in order to protect the public.…”
Section: Nutrition As a Complex Sciencementioning
confidence: 99%
“…77, [112][113][114][115][116][117][118][119][120] None the less, many herbal based companies are having preparations of G. cambogia that are currently on the global market. 76, [121][122][123] As a result of the immense hype of the weight-reducing potency of the nutraceutical, the adverse effects are going unnoticed and overlooked. The main aim of this review is therefore to educate the society by highlighting all possible adverse effects of the herbal drug by accessing all of the available research data's and clinical evidences.…”
Section: Introductionmentioning
confidence: 99%